Conjugated hybrid films based on a new polyoxotitanate monomer. Issue 100 (30th November 2018) - Liu, Gang; Yang, Xing; Bonnefont, Antoine; Lv, Yaokang; Chen, Jun; Dan, Wenyan; Chen, Zuofeng; Ruhlmann, Laurent; Wright, Dominic S.; Zhang, Cheng
Abstract : Electropolymerisation of the novel polyoxotitanate (POT ) hexamer [Ti(μ3 -O)(O i Pr)(TA)]6 (TA = thiophene-3-acetate) with 3, 4-ethylenedioxythiophene (EDOT ) gives films of hybrid conjugated copolymer, Poly-(EDOT-POT)s, the morphologies of which are, uniquely, influenced by the electropolymerisation potential. Abstract : Electropolymerisation of the novel polyoxotitanate (POT ) hexamer [Ti(μ3 -O)(O i Pr)(TA)]6 (TA = thiophene-3-acetate) with 3, 4-ethylenedioxythiophene (EDOT ) gives films of hybrid conjugated copolymer, Poly-(EDOT-POT)s, the morphologies of which are, uniquely, influenced by the electropolymerisation potential. NanoporousPoly-(EDOT-POT)-1 is a fast-ion electrode material and has improved electrochromic properties and significantly higher capacitance than that of the parent poly(3, 4-ethylenedioxythiophene) (PEDOT ).